COT-20 Clinical experience with tumor-treating fields therapy for newly diagnosed glioblastoma. (28th November 2020) - Saito, Norihiko; Hirai, Nozomi; Sato, Sho; Hiramoto, Yu; Fujita, Satoshi; Nakayama, Haruo; Hayashi, Morito; Sakurai, Takatoshi; Yagihashi, Akinori; Takahagi, Shusaku; Iwabuchi, Satoshi
Abstract: Introduction: Tumor-treating fields (TTF) is an established modality for glioblastoma (GBM) treatment administered through the portable Optune system. The efficacy of Optune for newly diagnosed GBM was demonstrated in the EF-14 phase 3 trial. Although TTF is now included as part of initial treatment in the Japan GBM guideline, it is not yet a standard therapy because the procedures are cumbersome and may impose unnecessary psychological burdens on patients with dire prognoses. In our institution, TTF therapy has been offered as a treatment option for GBM patients since January 2018. This report summarizes our initial experience with this novel treatment. Methods: The medical records of the first eight patients with newly diagnosed glioblastoma who underwent TTF were retrospectively reviewed. Results: The eight patients with newly diagnosed glioblastoma treated with TTF comprised five men and three women (median age, 68 years; range 34–83 years). Nine patients were offered TTF therapy, but one declined because of the need for a shaved head. The patients continued TTF for 1–7 months, without major complications. Skin reaction was the most prevalent adverse event (n = 5). One patient could not continue TTF treatment after femoral neck fracture due to the weight of the mobile battery. One patient who did not have a helper at home received TTF treatment from a nurse visiting his home. Conclusions: Patients should be provided with information on TTF, such as the timing of informed consent during and after chemoradiotherapy, to help them better understand this new modality and secure their consent.